Effect of preemptive topical application of lidocaine or prilocaine–lidocaine on successful catheterization of ear veins in New Zealand White rabbits. (September 2022) - Chung, Grace H.; Di Girolamo, Nicola; John, Shannon; Lucich, Dylan; Chang, Li-Jen; Brandão, João
Abstract: Objective: To compare 5% lidocaine ointment applied for 10 minutes before intravenous (IV) catheterization to a eutectic mixture of local anesthetics (2.5% lidocaine and 2.5% prilocaine; EMLA) cream applied for 10 or 60 minutes prior and a water-based placebo for 60 minutes for successful marginal ear IV catheterization in rabbits. Study design: Randomized, blinded, complete crossover, controlled trial. Animals: A total of 10 intact male, New Zealand White rabbits aged 4 months. Methods: After application of one of the treatments on the marginal ear vein, an operator unaware of the treatment attempted IV catheter placement. Successful IV catheterization was considered as a catheter inserted at the first attempt, safely secured, with appropriate patency. Generalized linear mixed models were developed to identify relevant predictors of successful catheter placement. Results: Ears that had EMLA cream applied 60 minutes before the catheterization attempt had more than 10 times the odds of successful catheter placement [odds ratio (OR)=10.75; 95% confidence interval (CI), 1.92–60.16; p < 0.008] compared with placebo. Both the application of EMLA cream or lidocaine ointment 10 minutes before the catheterization attempt resulted in approximately three times the odds of successful catheter placement compared with placebo, but were not statistically significant. Conclusions and clinical relevance: Application of EMLA cream on the marginal ear vein 60 minutes before catheterization increases the chance of successful IV catheter placement in conscious rabbits.